‘The burden of wanting to make it right’: thematic analysis of semistructured interviews to explore experiences of planning for crisis standards of care and ventilator allocation during the COVID-19 pandemic in the USA - Julia Chelen; Meredith MacMartin; Amber Barnato; Alison Zeng; Elizabeth Chuang (BMJ Open, 2023)
Objectives The COVID-19 pandemic prompted planning for clinical surges and associated resource shortages, particularly of equipment such as ventilators. We sought to examine the experience of the healthcare professionals who created policies for crisis standards of care, and allocation of ventilators in the event of shortage.Design To that end, we conducted semistructured interviews with healthcare professionals in the USA involved in institutional planning for resource shortages in the setting of the COVID-19 pandemic.Setting USA.Participants We conducted 25 interviews between May and July 2021. Half of the respondents were female (48%), many from Northeastern institutions (52%), and most practised in academic institutions (92%).Results Many (64%) respondents reported that their institution had an approved policy to guide ventilator allocation in the event of a shortage. We identified one overarching theme: the work of planning for resource shortages imposed a psychological burden on many planners. We identified four subthemes that influenced that burden: impact of leadership, institutional variation in process and policies, faith in the policies and future directions.Conclusions Improved leadership strategies and cross-institutional collaboration can reduce the psychological burden of planning and facilitate updating plans in anticipation of future shortages.